2007
DOI: 10.1016/j.jhazmat.2006.06.092
|View full text |Cite
|
Sign up to set email alerts
|

Removal of dieldrin from aqueous solution by a novel triolein-embedded composite adsorbent

Abstract: In this study, a novel triolein-embedded activated carbon composite adsorbent (CA-T) was prepared and applied for the adsorption and removal of dieldrin from aqueous systems. Experiments were carried out to investigate the adsorption behavior of dieldrin on CA-T, including adsorption isotherms, adsorption kinetics, the influence of initial concentration, temperature, shaking speed, pH and the addition of humic acid (HA) on adsorption. The adsorption isotherms accorded with Freundlich equation. Three kinetics m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The K f and n of Aerogel B on RhB were 1.16 and 0.73, respectively. On the other hand, Aerogel A exhibited a very strong adsorption capacity on dieldrin, the K f was 30.22, 11 times greater than that of active carbon, and 10 times greater than that of cellulose acetate [22]. Besides the high porosity and lipophilic surface, low density also played an important role for the high adsorption capacity exhibited by Aerogel A.…”
Section: Adsorption Equilibriummentioning
confidence: 96%
“…The K f and n of Aerogel B on RhB were 1.16 and 0.73, respectively. On the other hand, Aerogel A exhibited a very strong adsorption capacity on dieldrin, the K f was 30.22, 11 times greater than that of active carbon, and 10 times greater than that of cellulose acetate [22]. Besides the high porosity and lipophilic surface, low density also played an important role for the high adsorption capacity exhibited by Aerogel A.…”
Section: Adsorption Equilibriummentioning
confidence: 96%
“…Semi-permeable membrane devices (SPMD), which are based on the diffusion of hydrophobic substances from water to membrane bags filled with lipophilic phases, are widely used for monitoring organic contaminants in water (Huckins et al, 1990;Lu et al, 2002;Lu and Wang, 2003;Frank, 2005). Recently, a novel composite absorbent, triolein-embedded sorbent, is proposed for selectively removing trace POPs from water (Ru et al, 2007a(Ru et al, , 2007bHuo et al, 2005aHuo et al, , 2005bLiu et al, , 2007.…”
Section: Biomimetic Sorbent and Its Sorption Behaviors Of Persistent mentioning
confidence: 99%
“…Three sorbents were produced which were composed of supporting activated carbon (Ru et al, 2007a(Ru et al, , 2007b or silicon gel granules (Huo et al, 2005a(Huo et al, , 2005b) and the surrounding triolein-embedded cellulose acetate membrane, or CA-triolein sphere (Liu et al, , 2007, respectively. The analysis results of SEM and XPS for the sorbent showed that the triolein was wrapped in the thin CA polymer and constituted a significant fraction of the lipid pool in the sorbent.…”
Section: Design and Preparation Of Triolein-embedded Sorbentmentioning
confidence: 99%
“…According to the principle of similarity and intermiscibility, triolein has a strong absorbability for trace level of hydrophobic organic pollutants. Previous studies Liu et al, 2009;Huo et al, 2005;Ru et al, 2007;Qu, 2008) showed the preparation of a biomimetic adsorbent by embedding triolein into cellulose acetate (CA) spheres. The section structure is shown in Fig.…”
Section: Preparation and Application Of Lipoid Adsorbentmentioning
confidence: 99%